Global analysis of protein-RNA interactions in SARS-CoV-2-infected cells reveals key regulators of infection - Kamel, Wael; Noerenberg, Marko; Cerikan, Berati; Chen, Honglin; Järvelin, Aino I.; Kammoun, Mohamed; Lee, Jeffrey Y.; Shuai, Ni; Garcia-Moreno, Manuel; Andrejeva, Anna; Deery, Michael J.; Johnson, Natasha; et al. (Molecular cell, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes coronavirus disease 2019 (COVID-19). SARS-CoV-2 relies on cellular RNA-binding proteins (RBPs) to replicate and spread, although which RBPs control its life cycle remains largely unknown. Here, we employ a multi-omic approach to identify systematically and comprehensively the cellular and viral RBPs that are involved in SARS-CoV-2 infection. We reveal that SARS-CoV-2 infection profoundly remodels the cellular RNA-bound proteome, which includes wide-ranging effects on RNA metabolic pathways, non-canonical RBPs, and antiviral factors. Moreover, we apply a new method to identify the proteins that directly interact with viral RNA, uncovering dozens of cellular RBPs and six viral proteins. Among them are several components of the tRNA ligase complex, which we show regulate SARS-CoV-2 infection. Furthermore, we discover that available drugs targeting host RBPs that interact with SARS-CoV-2 RNA inhibit infection. Collectively, our results uncover a new universe of host-virus interactions with potential for new antiviral therapies against COVID-19.
Online veröffentlicht am 24. Mai 2021
Gesehen am 22.09.2021